South Asian ethnicity as a risk factor for coronary heart disease. (December 2020) - Pursnani, Seema; Merchant, Maqdooda
Abstract: Background and aims: South Asian ethnicity has been associated with increased cardiovascular risk, in the context of a greater burden of traditional cardiovascular disease risk factors. We aimed to identify the 10-year incidence of coronary heart disease (CHD) in South Asians, as compared to other racial-ethnic groups, in a retrospective cohort study, using the Kaiser Permanente Northern California integrated health care system, and to understand whether traditional risk factors could explain differences in outcomes. Methods and results: A study cohort established in 2006, with 10-year follow-up, identified a total n = 341, 309 patients, including 5149 South Asians, aged 30–70 years who underwent a screening lipid panel and had no prior history of CHD. There were a total of 460 (8.93%) patients with at least one cardiovascular event, including cardiovascular death, coronary artery revascularization, and myocardial infarction, in South Asians, as compared to 5.66% patients in the total population ( p  < 0.0001). In a multivariable logistic regression analysis, South Asian ethnicity, compared to White race, was associated with an adjusted odds ratio (aOR) = 2.04 (95%CI: 1.83, 2.28) in predicting the cardiovascular outcomes. Conclusions: South Asian ethnicity, even after adjustment for traditional risk factors, is associated with an increased risk of coronary heart disease outcomes. This risk was greater than other studied racial-ethnic groups and second only to diabetes in CHD risk prediction. Graphical abstract: Image 1 Highlights: South Asians carry a disproportionate burden of coronary heart disease worldwide. South Asian ethnicity may be an independent risk factor for coronary heart disease. Differential primary prevention strategies are essential in this high-risk ethnic group.